Re-visiting the concept of winescape through netnography: "A tale of two cities" - Ilinka Terziyska (Wine Economics and Policy, 2022)
Winescape is a central concept in wine tourism studies but is still under-researched, especially when package tours are concerned. This study has a two-fold objective: 1) to identify the winescape attributes of an emergent wine destination (Bulgaria) as perceived by organized wine tourists and compare them to a well-established Old-World wine region (Italy), and 2) to unveil the links between winescape attributes and servicescape dimensions. To this end, we employed a netnographic approach through the application of content analysis of TripAdvisor reviews and a combination of closed and open coding. Seven categories of winescape were identified, which almost completely coincide with the results of previous research. At the same time, some differences were found, mainly in the salience of the individual elements, which suggests a different composition of the winescape depending on several factors, among which the characteristics of the destination and the specifics of the tour operator. The study complements existing knowledge by validating a previously proposed model, and at the same time showcasing the context-dependent differences in attribute salience for two different types of destinations. In addition, it is the first to identify the links between the traditional supply-driven winescape models and the more holistic concept of experienscape.
Keywords: 330; winescape; wine tours; qualitative research; netnography; Bulgaria